MEDIA SOSIAL DAN PENGARUHNYA TERHADAP AKHLAK MAHASISWA DI KOTA METRO - Aprina Chintya; Latifatul Khoiriyah (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
Social media on the one hand brings a positive impact for students. But, on the other hand, it’s brings a negative impact if users are not selective and wise in use it. Abuse of the use of social media causes the decline of morals on the students. This study aims to see the influence of social media on morality students in Metro City. This research is field research, conducted at State Islamic Institute (IAIN) Metro, Ma'arif Institute of Islam (IAIM) Nahdatul Ulama Metro and Muhamadiyah Metro University. Primary data source is done by interview to student and secondary data source obtained by conducting literature study. Data analysis is done from the beginning to the end of the research with triangulation of data. Furthermore, data analysis results are described in the discussion. The result show that the high intensity of social media users (social networking) on students in Metro City affect the morals of students, both the influence of negative and negative. Therefore, students must be selective and wise in order to utilize social media only for positive things.